x2 - 5x = 0Factor the left side:x (x - 5) = 0x = 0x = 5
x3+13x2=-22xadd 22x to both sides:x3+13x2+22x=0now factor:x(x2+13x+22)=0x(x+11)(x+2)=0x=0x+11=0x+2=0Therefore the solution to this equation is x=0, x=-11, x=-2
Answer : x = ± 1 4x2 - 30 = 34 : 4x2 = 34 - 30 = 4 4x2 = 4 : x2 = 1 therefore x = √1 = ± 1
This is how I did it:8x3+4x2+6x+3[8x3+4x2]+[6x+3][(4x2)(2x+1)]+[(3)(2x+1)]....as you can see, this is in the general form of ab+cb, which factored is b(a+c), so:(2x+1)(4x2+3)
f'(x)= 0x^-1=0anything multiplied by zero equals zero
(2x - 5)(2x + 5)
(2x + 5)(2x - 5)
4x2 = 8, 8-9 = -1 therefore the answer is "-1"
We're on it . . .6x3 + 4x2 = 2xSubtract 2x from each side:6x3 + 4x2 - 2x = 0Divide each side by 2:(Don't divide by 'x' ... you'll lose a root.)3x3 + 2x2 -x = 0Factor the left side:x (3x2 + 2x - 1) = 0x (3x - 1) (x + 1) = 0x = 0x = 1/3x = -1
4x2 - 36x + 81 = 4x2 - 18x - 18x +81 = 2x(2x - 9) - 9(2x - 9) = (2x - 9)2
4x2-36x+81 (2x-9)(2x-9)
4x2 - 3x - 9
x2-14x+45=0(x-9)(x-5)=0x-9=0 & x-5=0x=9 & x=5
The expression is likely 4x2 - 36x +81 which is the same as (2x - 9)(2x - 9) or (2x - 9)2
Only if the value of c is 9 because:- 4x2+12x+9 = (2x+3)(2x+3)
4x2+49x+90 = (4x+9)(x+10) when factored
3x3=9 So, it could only be 9x1 which=9. 3x1=3 3 does not equal 9. 4x2=8 8 does not equal 9. 6x3=18 18 does not equal 9